menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Solve by using substitution y=2x 3x-y=3
asked
May 11, 2022
116k
views
3
votes
Solve by using substitution
y=2x
3x-y=3
Mathematics
high-school
Laszlok
asked
by
Laszlok
4.8k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
2
votes
answer:
x = 3
y = 6
Explanation:
we have two equations —
y = 2x
3x - y = 3
we have to use substitution so we will replace y with 2x since y = 2x
3x - 2x = 3
now that we have like terms, we can solve this to find x
3x - 2x = 3
x = 3
now, we will use this to find y
y = 2x
y = 2(3)
y = 6
Hathor
answered
May 16, 2022
by
Hathor
4.6k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.1m
questions
6.7m
answers
Other Questions
Pizza planet is running a special 3 pizzas for 16.50. What is the unit rate for one pizza
What number is halfway between 0 and 18
If the 9-inch wheel of cheese costs $18.60, what is the cost per square inch? If the cost is less than a dollar, put a zero to the left of the decimal point?
I need to simplify this expression.
Need answer to math problem!!!
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org